2013
DOI: 10.1007/s10753-013-9728-6
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Fenofibrate Against TNF-α-Induced CD40 Expression through SIRT1-Mediated Deacetylation of NF-κB in Endothelial Cells

Abstract: Fenofibrate, as a lipid-lowering drug in clinic, participates in the regulation of inflammatory response. Recently, increasing studies have indicated that sirtuin1 (SIRT1), a NAD+-dependent deacetylase, has potential anti-inflammatory effect in endothelial cells. However, whether the regulatory effect of fenofibrate on inflammation response is mediated by SIRT1 remains unclear. The aim of this study was to investigate the effect of fenofibrate on the expressions of SIRT1 and pro-inflammatory cytokine CD40 in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…Fenofibrate, a well-known agonist of PPARα, ameliorates the IL-1-induced inflammatory response in human aortic smooth muscle cells by inhibiting IL-6 expression 32 and reduces plasma triglyceride with a concomitant increase in high-density lipoprotein-cholesterol in humans with metabolic syndrome 16 . Furthermore, fenofibrate shows protective effects against TNFα-induced inflammation via sirtuin1 (SIRT1)-associated inhibition of NFkB activity in endothelial cells 33 . Fatty acid oxidation and energy consumption resulting from PPARα activation in skeletal muscle and adipose tissue has many beneficial effects, including improved exercise endurance, insulin sensitivity, and reduced body weight 17, 19, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Fenofibrate, a well-known agonist of PPARα, ameliorates the IL-1-induced inflammatory response in human aortic smooth muscle cells by inhibiting IL-6 expression 32 and reduces plasma triglyceride with a concomitant increase in high-density lipoprotein-cholesterol in humans with metabolic syndrome 16 . Furthermore, fenofibrate shows protective effects against TNFα-induced inflammation via sirtuin1 (SIRT1)-associated inhibition of NFkB activity in endothelial cells 33 . Fatty acid oxidation and energy consumption resulting from PPARα activation in skeletal muscle and adipose tissue has many beneficial effects, including improved exercise endurance, insulin sensitivity, and reduced body weight 17, 19, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al demonstrated that amyloid beta- (A β -) induced IL-8 and IL-6 expression was attenuated in cells pretreated with SIRT1 activators and that SIRT1 knockdown exacerbated the A β -induced proinflammatory effects [46]. Recently, several studies have shown that fenofibrate exerted protective effects against TNF- α -induced CD40 expression through SIRT1-mediated deacetylation of the NF- κ B-p65 subunit [47]. Similarly, we have found that fenofibrate and HQT (HM/HH groups) increased SIRT1 and decreased Ac-NF- κ B-p65, TNF- α , IL-1 β , and IL-6, which suggests that the beneficial effect of HQT on anti-inflammation might be partly attributable to the upregulated expression of SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates cellular inflammation in endothelial cells, and the anti-inflammatory property of SIRT1 is closely related to its inhibition of NF-κB [11][12][13].…”
Section: Introductionmentioning
confidence: 99%